Analysing students’ mobility at higher education institutions: case of Ukrainian university during the war - Chala, Nina; Pichyk, Kateryna; Poddenezhnyi, Oleksandr; Voropai, Olga (Journal of Business Economics and Management, 2024)
Higher Education Institutions (HEIs) often overlook the importance of systematic data collection and analysis. This oversight can obscure critical trends and decision-making insights, particularly student mobility. HEIs management may not detect the outflow of students related to academic mobility and therefore will not make timely managerial decisions. This article aims to provide guidance to university management on how data collection and analysis can improve informed decision-making, focusing on student mobility, especially in times of severe disruptions, like military conflicts. To reach this goal, desk research of previous literature was conducted to identify risks and challenges related to students’ mobility and the previous experience to address them. Secondary data analysis of student outflow at the Faculty of Economics of the National University “Kyiv-Mohyla Academy” (NaUKMA) from 2015–2022, alongside a student survey provided insights into the students’ academic mobility process dynamics. The findings demonstrate a significant outflow of students from educational programs, highlighting the opportunities and risks associated with academic mobility. Analysis of this data reveals critical insights into student motivation, which can significantly influence their decisions and behavior. Students’ mobility data analysis will instantly point out the problem to HEI management, making it possible to prevent the consequences.